Demographics of a large paediatric Postural Orthostatic Tachycardia Syndrome Program - Boris, Jeffrey R.; Bernadzikowski, Thomas (Cardiology in the young, 2018)
The aim of this study was to identify and evaluate demographic and clinical features of paediatric patients with postural orthostatic tachycardia syndrome in a tertiary hospital speciality clinic. This is a retrospective review of clinical data obtained during initial outpatient evaluation. A total of 708 patients met the evaluation criteria. Female patients outnumbered males, 3.45:1. Caucasians were over-represented at 94.1% of patients. Median age at diagnosis was 15.7 years. Joint hypermobility occurred in 57.3% of patients; 22.4% had hypermobile Ehlers-Danlos syndrome; and 34.9% had hypermobility spectrum disorder. Median age of onset of symptoms was 12.6 years in patients with hypermobility versus 13.7 years in those without (p=0.0001). Median duration of symptoms was 3.3 years with hypermobility versus 1.5 years without (p<0.00001). Putative triggers included infection in 23.6% of patients, concussion in 11.4%, and surgery/trauma in 2.8%. Concurrent inflammatory disorders were noted in 5.2% of patients. Six symptoms comprised 80% of initial patient complaints. Overall, 66% of patients subsequently had at least 10 symptoms, 50% had at least 14 symptoms, and 30% reported at least 26 symptoms. Symptoms were largely cardiovascular, gastrointestinal, and neurological. Paediatric patients with postural orthostatic tachycardia syndrome seen in a large speciality clinic are predominantly female, are mostly Caucasian, have onset of symptoms in early adolescence, and have symptoms for over two years before diagnosis. Over half of patients have joint hypermobility. More than one-third of patients have a possible autoimmune or inflammatory trigger, including infection, concussion, or surgery/trauma. Patients experience symptoms that are highly variable and multi-system in origin over the course of illness.